Lithosphere Mantle Density of the North China Craton. Issue 9 (7th September 2020) - Xia, Bing; Thybo, Hans; Artemieva, Irina M.
Abstract: We constrain the lithospheric mantle density of the North China Craton (NCC) at both in situ and standard temperature‐pressure (STP) conditions from gravity data. The lithosphere‐asthenosphere boundary (LAB) depth is constrained by our new thermal model, which is based on a new regional heat flow data set and a recent regional crustal model NCcrust. The new thermal model shows that the thermal lithosphere thickness is <120 km in most of the NCC, except for the northern and southern parts with the maximum depth of 170 km. The gravity calculations reveal a highly heterogeneous density structure of the lithospheric mantle with in situ and STP values of 3.22–3.29 and 3.32–3.40 g/cm 3, respectively. Thick and reduced‐density cratonic‐type lithosphere is preserved mostly in the southern NCC. Most of the Eastern Block has a thin (90–140 km) and high‐density lithospheric mantle. Most of the Western Block has a high‐density lithospheric mantle and a thin (80–110 km) lithosphere typical of Phanerozoic regions, which suggests that the Archean lithosphere is no longer present there. We conclude that in almost the entire NCC the lithosphere has lost its cratonic characteristics by geodynamic processes that include, but are not limited to, the Paleozoic closure of the Paleo‐Asian Ocean in the north, the Mesozoic Yangtze Craton flat subduction in the south, the Mesozoic Pacific subduction in the east, the Cenozoic remote response to the Indian‐Eurasian collision in the west, and the Cenozoic extensional tectonics (possibly associated with the slab roll‐back) in the center. Key Points: STP lithospheric mantle density of the NCC ranges from 3.32 to 3.40 g/cm 3 Most of the NCC lithosphere lost cratonic characteristics Lithosphere density anomalies do not follow geological boundaries